Meta-Analysis Factor of Hand Washing Habits and Exclusive Breastfeeding with Diarrhea Between 2017-2021 in Indonesia - Ranimas Ayu Wulandari; R. Azizah; Juliana Binti Jalaludin; Lilis Sulistyorini; Khuliyah Candraning Diyanah (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Diarrhea is an endemic disease that causes extraordinary events (pandemic) and is often accompanied by death in Indonesia. Previous reports showed that children who practice poor hand washing or without using soap and running water are 2.175 times more likely to experience diarrhea. It was also discovered that exclusive breastfeeding can form antibodies and other nutrients that protect babies from infections such as diarrhea. Therefore, this study aimed to analyze the most influential factors between hand washing habits and exclusive breastfeeding on the incidence of diarrhea in Indonesia. Methods: This study used a meta-analysis method. Results and Discussions: The results showed that the pooled PR value of the hand washing habit variable e1.06 = 2.886 (95% CI 0.87 - 1.24) was greater than the exclusive breastfeeding e0.53 = 1.698 (95% CI 0.36 – 0.70). The data were obtained from articles and journals with a cross-sectional study design. Based on the results of the meta-analysis, people who did not apply proper hand washing habits are 2,886 times more at risk of diarrhea. Furthermore, babies who were not exclusively breastfed were 1,698 times more likely to have diarrhea than those who received exclusive breastfeeding. Conclusion: The results showed that the most influential factor between the two variables was the hand washing habit variable.